High-Performance Liquid Chromatography of Peptides and Proteins. Pharmaceutical and Bio-medical Applications - Kenneth J. Wilson; Graham J. Hughes (CHIMIA)
The power of the technique of high-performance liquid chromatography as an analytical tool is becoming widely recognized. In the field of peptide synthesis the method is being employed for both quality control and preparative isolation. Similarly, naturally occuring polypeptide hormones are being isolated and characterized employing the method. Its use in identifying amino acid residues in proteins which were post translationally modified with pharmaceutical agents has been illustrated. Procedures, as employed in our laboratories, are given and applications illustrated for various problems which have arisen related to polypeptides, or chemical reactions thereon, which are of bio-medical/pharmaceutical relevance.